Transpozice os pisiforme pri resení rozvinutých stadií morbus Kienböck - dlouhodobé výsledky - Barták, Vladislav; Pech, J; Veigl, D; Hromádka, R; Pokorný, D; Sosna, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2009)
PURPOSE OF THE STUDY: One of the methods used for treatment of Kienböck's disease is based on transposition of the pisiform bone into free space created by removal of the lunate bone. It is performed in patients with stage IIIB to IV, as assessed by Lichtmann's score. However, this operative procedure has so far lacked an unequivocal assessment of its therapeutic value. The aim of our work was to assess the therapeutic effect of the Kuhlmann method in the treatment of advanced stages of Kienböck's disease. MATERIAL: From January 1996, eighteen patients (18 wrists) diagnosed with Kienböck's disease were operated on, using the Kuhlmann method, and the group of these patients was included in this follow-up study. The average follow-up time was 7.6 +/- 2.3 years. METHODS: The results were evaluated on the basis of subjective (VAS) and functional criteria (ROM, grip force, DASH questionnaire and combined Cooney score questionnaires) and radiological assessment (arthritis evaluation, C.H.I., Natrass index, RSA). RESULTS: All patients experienced pain relief. The average pain assessment by VAS (10-point scale) before and after the procedure was 8.76 +/- 0.9 and 2.94 +/- 1.59, respectively. The range of motion was reduced on the operated extremity (70% compared to non-operated) as well as the grip test (57%). The average DASH score at the time of study was 20.9 +/- 12.2 and the average Cooney score was 67.6 +/- 17.4. Before the operation, eleven wrists showed signs of osteoarthritis. At the follow-up evaluation, arthritis was present in fifteen patients.We found a significant difference in average radiological parameters characterizing a carpal collapse deformity (C.H.I., Natrass index, RSA) - all parameters showed deteriorating tendencies. DISCUSSION: In nine patients, necrotic changes of the lunate occurred. In the patients whose pisiforme was not affected, a moderate retardation of carpal collapse occurred. However, the discrepancy between relevant indicators (C.H.I, Natrass index, RSA) was not statistically significant when comparing both groups. Therefore, we cannot conclude as to whether or not a vital transposed pisiforme bone impedes the development of carpal collapse. The only proved difference between these two groups was in pain evaluation, measured by VAS, after the procedure CONCLUSION: Although there was a good subjective assessment of the operation results, we are of the opinion that this method should not be used as a routine surgical procedure for advanced Kienböck disease. In view of a large number of failed cases we believe that this method should be considered very carefully.
Keywords: lidé; mladiství; Adult; Middle Aged; Pisiform Bone; Lunate Bone; Adolescent; Carpal Bones; Humans; hráškovitá kost; kosti zápěstní; Radiography; radiografie; lidé středního věku; mladý dospělý; Osteonecrosis; Young Adult; osteonekróza; poloměsíčitá kost; dospělí